REALIZING THE PURPOSE OF ISLAMIC EDUCATION THROUGH BOARDING SCHOOL MANAGEMENT - Nur Asih Istiqomah; Farid Setiawan (LPPM Universitas Negeri Jakarta, 2021)
This research aims to determine the implementation of boarding school management to realize Islamic education purpose in one of the boarding schools, namely Muhammadiyah Boarding School Yogyakarta. The research method used is field research with a qualitative type based on data collection techniques in interviews, observation, and documentation. The results showed a substantial relationship between boarding school management and national education goals in general and the goals of Islamic education in particular. There are efforts to achieve the four dimensions of Islamic education goals. First, Physical education discusses Fiqh and ushul fiqh lessons. Second, spiritual education with Islamic practices such as fasting Monday Thursday. Third, through religious studies, academic education is based on arguments and history of mujtahid priests such as Imam Maliki, Imam Shafi'i, Imam Hanafi, and Imam Hambali. Fourth, social education through joint activities both in dormitories at schools and in the community. Providing soft skills that help develop children's intellectuals with activities that include tahfidz (memorizing the Koran), language areas (mandatory English and Arabic language environments), speech, and others. Likewise, hard skills provisioning in the form of extracurricular activities for Tapak Suci and Hizbul Wathan. With the implementation of boarding school management, it's hoped that the school can achieve Islamic education purpose.